POSITION OF ADOPTED CHILDREN IN THE DISTRIBUTION OF HERITAGE PROPERTY IN INDONESIA - Cucuk Kristiono (International Journal of Law Reconstruction, 2018)
Adoptions are included in the category of legal acts, the which resulted in the rightsand obligations of the parties. In the Burgelijk Weetboekand the compilation of Islamic law, are differences in theregulations about how the positions Adopted child to the adoptive parents. It is implicated in the process of inheritance. Adopted inheritance of the children in accordance with Islamic Law Compilationused was was borrowed, while the Burgelijk Wetboeek, inheritthe same Adopted children with legitimate children.